2012
DOI: 10.1111/j.1556-4029.2012.02058.x
|View full text |Cite
|
Sign up to set email alerts
|

Study of Poroscopy Among South Indian Population*

Abstract: Poroscopy is the term applied to a specialized study of pore structure found on papillary ridges of skin as a means of identification. It comes under level 3 detail of identification and hence is more reliable and accurate. The goal of this study is to estimate the importance of poroscopy for identification of individuals and to determine the gender based on frequency, type, and shape of pores. Left plain thumb prints of 200 individuals (100 men and 100 women) aged between 18 and 60 belonging to South Indian p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Keeping in mind the nature, permanency, immutability, and variability of sweat pores, poroscopy will be a possible mean of personal identification in several cases where complete or adequate friction ridge impression is missing on the crime scene or such cases. Previously, several studies have been performed to verify such a correlation between sweat pores and different fingers (Preethi et al 2012). In their research, they have estimated the importance of poroscopy for the identification of individuals and to determine the gender based on frequency, type, and shape of pores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Keeping in mind the nature, permanency, immutability, and variability of sweat pores, poroscopy will be a possible mean of personal identification in several cases where complete or adequate friction ridge impression is missing on the crime scene or such cases. Previously, several studies have been performed to verify such a correlation between sweat pores and different fingers (Preethi et al 2012). In their research, they have estimated the importance of poroscopy for the identification of individuals and to determine the gender based on frequency, type, and shape of pores.…”
Section: Discussionmentioning
confidence: 99%
“…Many pieces of research have focused on studying the characteristic of friction ridge mainly the sweat pores among different sex, ages, and populations (Bindra et al 2000;Wijerathne 2015;Tafazoli et al 2013;Nagesh et al 2011;Preethi et al 2012). Several studies showed that there is no significant difference in the pore characteristics morphology on the epidermal friction ridges between males and females and that the number of pores does not significantly vary.…”
Section: Introductionmentioning
confidence: 99%
“…• Significant difference: Circular or round pores possessed higher occurrence in males than females [98] • No significant difference [97] …”
Section: Applications Of Level 3 Featuresmentioning
confidence: 99%
“…He is considered to be the father of poroscopy (10). The sexual dimorphism of characteristics of pores have been evaluated in several studies (11,(17)(18)(19). Bindra et al conducted a study to compare the characteristics of pores between inked and latent prints among Indians (17).…”
Section: Poroscopy: An Important Research Field In Medicine and Physimentioning
confidence: 99%
“…Nagesh et al evaluated sex differences and influences of persons age on pore characteristics (18). Preethi et al studied pores among South Indians to establish sex differences in frequency, types and shapes of pores (19). Tafazoli et al studied pores among Iranians to establish the frequency, types, position and shapes of pores (20).…”
Section: Poroscopy: An Important Research Field In Medicine and Physimentioning
confidence: 99%